2017
DOI: 10.15414/jmbfs.2017.7.1.22-26
|View full text |Cite
|
Sign up to set email alerts
|

Industrial Apple Pomace by-Products as a Potential Source of Pro-Health Compounds in Functional Food

Abstract: Keywords: fruit residues, novel food, phloridzin, dietary fibre

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 17 publications
1
21
0
6
Order By: Relevance
“…It is rich in healthy bioactive compounds (Konrade, Klava, & Gramatina, 2017). The studies revealed that phenolic substances are mainly found in apple peels in comparison to the rest of the apple (Cao et al., 2009; Kruczek et al., 2017). Van der Sluis et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is rich in healthy bioactive compounds (Konrade, Klava, & Gramatina, 2017). The studies revealed that phenolic substances are mainly found in apple peels in comparison to the rest of the apple (Cao et al., 2009; Kruczek et al., 2017). Van der Sluis et al.…”
Section: Introductionmentioning
confidence: 99%
“…(2002) reported that juices produced from two apple species had about 3% to 10% of antioxidant capacity of the whole fruit. Dietary fibers that can be found in apple pomace contain well‐balanced soluble and insoluble fibers and represent constituents with higher quality when compared to popular cereal ones (Kruczek et al., 2017). Those facts created researches concerning the use of the apple pomace as a functional ingredient in different food types with the purpose of fortification and increase of their nutritive value, which for the main goal had a creation of products with increased value and which are acceptable to the consumers.…”
Section: Introductionmentioning
confidence: 99%
“…Dietary fibre has many health benefits and could help in the treatment of obesity, atherosclerosis, coronary heart diseases, large intestine cancer, and diabetes by decreasing blood glucose level. It can bind hydrochloric acid, metal ions, and cholesterol in the stomach and can also stimulate growth of probiotic microflora in the intestines [7]. An adequate intake for total dietary fibre is set at 28 and 25 g per day for young men and women, respectively [8].…”
Section: Introductionmentioning
confidence: 99%
“…Concretely, in Spain more than 20,000 metric tonnes of apple pomace are produced every year as a by-product of cider production, with Asturias being the largest producer, followed by the Basque Country [13] . Although the composition of the apple pomace varies depending on different factors it contains minerals, is rich in nutrients and also contains a large amount of carbohydrates, of which about 70% are simple sugars, with fructose being the predominant sugar, followed by glucose, sucrose, arabinose, galactose and xylose [14] .…”
Section: Introductionmentioning
confidence: 99%